Indicative and Updated Estimates of the Collective Bargaining Premium in Germany - John T. Addison; Paulino Teixeira; Katalin Evers; Lutz Bellmann (Institute for the Study of Labor (IZA), 2013)
This study provides updated evidence on the union contract differential in Germany using establishment-wide wage data and two estimation strategies. It provides pairwise estimates of the union differential based on separate samples of collective bargaining leavers and joiners vis-à-vis the corresponding counterfactual groups. It is reported that average wages increase by 3 to 3.5 percent after entering into a collective agreement and decrease by 3 to 4 percent after abandoning a collective agreement. Excluding establishments that experience mass layoffs little influences these net findings, although such establishments record wage losses - statistically insignificant for joiners but up to 10 percent in the case of leavers, as compared with the counterfactuals. The backdrop to these new indicative estimates, which are properly conditioned on establishment size and industry affiliation, inter al., is one of wage stagnation and continuing union decline.
Keywords: J31; J51; 330; average wages; union contract premium; collective bargaining transitions; difference-in-differences; matching; Germany